Расплескавшийся цветом. К.В. Душенко Красное и белое. Из истории политического языка: Сборник статей / РАН. ИНИОН. Москва: Центр гуманитарных научно-информационных исследований, 2018 - Smirnov, Ivan (Przegląd Rusycystyczny, 2021)
This review presents the author's views on the book Red and White, which deals with the multivariance of color symbolism of the political language of revolutions in France and Russia. Writers' ideas about color political language of that historical period are reflected in their literary works. The characteristic features of white, red, black and blue colors, which carry an active visual call at all times, are highlighted and described. Conducting his own analysis of the identity of the color palette of the French tricolor and Russian tricolor flags, the author of the article is based on the principles of perception of color by representatives of various ethnic groups, based on the experience of processing external impressions and mentality.